Simulation Study of n-ZnO/p-Si Heterojunction Solar Cell - Pogrebnyak, A.D.; Jamil, N.Y.; Muhammed, A.K.M. (Наносистеми, наноматеріали, нанотехнології, 2011)
In a given paper, the simulation program SCAPS—10 is used to study the structure of the n-ZnO/p-Si heterojunction solar cell. This program is designed basically for the simulation and studying the properties of photonic devices. We explored such important controllable design parameters affecting the performance of the p—n-junction solar cells as operating temperature, as we notice increasing in J—V characteristics with T increasing, the effect of thickness of each layer on the performance of a cell is studied, as well as an increasing of J—V characteristics with increasing of p-layer thickness. In the numerical example, 3 um p-layer and 3 um n-layer work to the best advantage for a given doping density. If we change the optimum value, the efficiency can reach η = 5.83% with Voc = 0.589 V, Jsc = 12.451 mA at 300 K, Na = Nd = 10¹⁹; in this case, we have come out the optimum parameters to achieve the best performance of this type of a cell, and we made comparison with a practical ZnO/Si cell.